2017
DOI: 10.1155/2017/9260701
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable Concentrations of Delphinidin and Its Metabolite, Gallic Acid, Induce Antioxidant Protection Associated with Increased Intracellular Glutathione in Cultured Endothelial Cells

Abstract: Despite limited bioavailability and rapid degradation, dietary anthocyanins are antioxidants with cardiovascular benefits. This study tested the hypothesis that the antioxidant protection conferred by the anthocyanin, delphinidin, is mediated by modulation of endogenous antioxidant defences, driven by its degradation product, gallic acid. Delphinidin was found to degrade rapidly (t1/2 ~ 30 min), generating gallic acid as a major degradation product. Both delphinidin and gallic acid generated oxygen-centred rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 83 publications
2
39
0
Order By: Relevance
“…On the other hand, it seems that the indirect mechanisms, involving the modulation of cellular signaling pathways and the activity of some transcription factors (Nrf2, NF-kB, Sp1) could be more relevant in vivo. Moreover, recent studies indicated that ACNs’ metabolites, rather than ACN, are responsible for the observed beneficial effects [114,115,116,117,118,119,120]. Also, it is important to underline the fact that only some studies used ACNs or their metabolites at physiologically relevant concentrations [115,116,118,119].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…On the other hand, it seems that the indirect mechanisms, involving the modulation of cellular signaling pathways and the activity of some transcription factors (Nrf2, NF-kB, Sp1) could be more relevant in vivo. Moreover, recent studies indicated that ACNs’ metabolites, rather than ACN, are responsible for the observed beneficial effects [114,115,116,117,118,119,120]. Also, it is important to underline the fact that only some studies used ACNs or their metabolites at physiologically relevant concentrations [115,116,118,119].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…Cell survival after treatment with H 2 O 2 (400 μM) was assessed using the MTT cell assay, using a procedure similar to previous publications. 16,46 SH-SY5Y cells were seeded (7000 cells per well) in a 96-well plate. After adhesion (24 h), cells were treated with different concentrations of compound 4, ranging from 0.01 to 5 μM, and incubated for 24 h. Subsequently H 2 O 2 solution was added to the positive control and the test drug wells, followed by incubation for another 24 h. After incubation, all the solutions were removed from all the wells and 100 μL of MTT solution (1 mg mL −1 ) was added in each well.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Besides the interaction with gut microbiota, direct effects of anthocyanin structures or metabolites are additionally described [ 14 , 15 ]. It is becoming clearly recognized that anthocyanins can interact with various molecular targets and affect multiple signalling pathways [ 16 , 17 , 18 , 19 , 20 , 21 ]. To further evaluate the clinical benefits observed with the MBE [ 6 , 7 , 8 , 9 ] it is of high interest to specifically examine the uptake of unmetabolized anthocyanin structures present in the extract.…”
Section: Introductionmentioning
confidence: 99%